Methodologies and Intelligent Systems for Technology Enhanced Learning 6th International Conference - Caporuscio, Mauro; De la Prieta, Fernando; Di Mascio, Tania; Gennari, Rosella; Gutiérrez Rodríguez, Javier; Vittorini, Pierpaolo (Advances in Intelligent Systems and Computing, 2016)
The 6th International Conference in Methodologies and intelligent Systems for Technology Enhanced Learning held in Seville (Spain) is host by the University of Seville from 1st to 3rd June, 2016. The 6th edition of this conference expands the topics of the evidence-based TEL workshops series in order to provide an open forum for discussing intelligent systems for TEL, their roots in novel learning theories, empirical methodologies for their design or evaluation, stand-alone solutions or web-based ones. It intends to bring together researchers and developers from industry, the education field and the academic world to report on the latest scientific research, technical advances and methodologies.